A murky business. Issue 1 (February 2015) - Jeong, Yujin; Gastwirth, Joseph L.
<x xml:space="preserve">Abstract</x> Corruption in Iraq's Oil‐for‐Food Programme was exposed a decade ago. But key information remains unpublished – information that could shed further light on the impact of bribes paid to Saddam Hussein's regime. By Yujin Jeong and Joseph L. Gastwirth